Mass balance, ice volume, and flow velocity of the Vestre Grønfjordbreen (Svalbard) from 2013/14 to 2019/20 - Anton V. Terekhov; Sergei Verkulich; Alexander Borisik; Vasiliy Demidov; Uliana Prokhorova; Kseniia Romashova; Mikhail Anisimov; Olga Sidorova; Gleb Tarasov (Arctic, Antarctic, and Alpine Research, 2022)
ABSTRACTThe first seven years (2013/14–2019/20) of annual and seasonal mass-balance monitoring on the glacier Vestre Grønfjordbreen (16.4 km2), located south of the town of Barentsburg on Spitsbergen, Svalbard, are presented. This part of the archipelago is one of the least glaciated on Svalbard and at the same time it experiences the most prominent glacier retreat within the last few decades. The annual mass balance of Vestre Grønfjordbreen is negative, ranging from −0.60 ± 0.18 to −2.01 ± 0.26 m w.e. The results of direct observations are compared with the geodetic mass balance for the same period (July 2015 through end of summer 2019) to identify systematic bias in the record. As the mismatch between cumulative mass balances, defined by the glaciological method (−5.66 ± 0.47 m w.e.) and computed from geodetic differencing (−5.52 ± 0.40 m w.e.), lies within the uncertainty limits, no calibration of the mass-balance series is needed. From the results of a ground-penetrating radar (GPR) survey (spring 2019), which confirmed the polythermal glacier structure, a total glacier volume of 1.987 ± 0.139 km3 was found, meaning that the cumulative mass loss during the reported seven-year period equals 8 ± 1% of the total glacier mass. Observed annual ice-flow velocities, varying from 0.50 ± 0.10 to 4.50 ± 0.10 m year−1, are consistent with low mean bed and surface slopes (5° and 8°, respectively). Correlations of mass-balance values with meteorological observations at the Barentsburg weather station are mediocre, possibly due to anomalous values recorded for 2015/16: the negative mass-balance peak reported for the other land-terminating Svalbard glaciers was not observed at Vestre Grønfjordbreen.